IMPROVING SPEAKING SKILL USING SHADOW PUPPET - Winarsih, Ayu (UNIVERSITAS SLAMET RIYADI, 2017)
AbstractSpeaking is one of productive skills in which it is used to communicate with others. The purpose of speaking is to share knowledge, information and ideas. However, the eight grade of SMP N 1 Kedawung still found it difficult. The aims of this research were to know whether Shadow Puppet could improve students speaking skill and to describe the class condition when Shadow Puppet was implemented in teaching learning process at the eight grade students of SMP N 1 Kedawung in 2017/2018 Academic Year. This research was conducted at the eight grade of SMP N 1 Kedawung. The method of the study was classroom action research which was conducted from January up to February 2018. The data were collected through test (oral test) and non-test (observation, interview, and documentation). While, to analyze the data t-test was used. The result of this study showed that the implementation of Shadow Puppet was succsessful to improve the students’ speaking skill. The mean score increased from 54.3 in pre-test became 63.1 in post-test 1 and became 75.48 in post-test 2. The analyzing score using t table was 2,645 <115,324> 2,756 meanwhile, cycle 2 was 2,045 <12,236> 2,756. It can be concluded that Shadow Puppet was appropriate to improve the students’ speaking skill in teaching and learning process. Moreover, the class condition were more attractive and more fun during teaching and learning process. Keywords: Speaking Skill, Shadow Puppet, Classroom Action Research. ABSTRAKBerbicara adalah salah satu keterampilan produktif yang digunakan untuk berkomunikasi dengan orang lain. Tujuan berbicara adalah untuk berbagi pengetahuan, informasi, dan ide. Namun, kelas delapan SMP N 1 Kedawung masih merasa kesulitan. Tujuan dari penelitian ini adalah untuk mengetahui apakah Shadow Puppet dapat meningkatkan keterampilan berbicara siswa dan untuk menggambarkan kondisi kelas ketika Shadow Puppet diterapkan dalam proses belajar mengajar di delapan siswa kelas SMP N 1 Kedawung pada Tahun Akademik 2017/2018. Penelitian ini dilakukan di kelas delapan SMP N 1 Kedawung. Metode penelitian ini adalah penelitian tindakan kelas yang dilakukan dari Januari hingga Februari 2018. Data dikumpulkan melalui tes (tes lisan) dan non-tes (observasi, wawancara, dan dokumentasi). Sedangkan untuk menganalisis data digunakan uji-t. Hasil penelitian ini menunjukkan bahwa penerapan Shadow Puppet berhasil meningkatkan keterampilan berbicara siswa. Skor rata-rata meningkat dari 54,3 pada pre-test menjadi 63,1 pada post-test 1 dan menjadi 75,48 pada post-test 2. Skor analisis menggunakan t tabel adalah 2,645 <115,324> 2,756 sementara itu, siklus 2 adalah 2,045 <12,236> 2,756. Dapat disimpulkan bahwa Shadow Puppet tepat untuk meningkatkan keterampilan berbicara siswa dalam proses belajar mengajar. Selain itu, kondisi kelas lebih menarik dan lebih menyenangkan selama proses belajar mengajar. Kata kunci: Keterampilan Berbicara, Wayang Kulit, Penelitian Tindakan Kelas.